ANALISIS KINERJA KEUANGAN PADA PT BLUE BIRD TBK PERIODE 2015-2024 - Mutiara, Mutiara; Puji Muniarty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the financial performance of PT Bluebird Tbk during the 2015-2024 period using a descriptive research method. The data used in this research are secondary data obtained from the company's financial statements published annually. The analysis focuses on financial ratios, including liquidity ratios, profitability ratios, and solvency ratios, to evaluate the company's financial condition.The results show that PT Bluebird Tbk experienced fluctuations in financial performance throughout the observed period, especially during the COVID-19 pandemic, which significantly impacted revenue and profitability. However, the company demonstrated resilience by gradually improving its financial condition in the post-pandemic period. Liquidity ratios indicate that the company remains capable of meeting its short-term obligations, while profitability ratios show recovery trends in recent years. Solvency ratios suggest that the company maintains a manageable level of debt. This study provides insights into the financial stability and performance trends of PT Bluebird Tbk and can be used as a reference for investors and stakeholders in decision-making.